POTENTIAL FOR PLAGIARISM OF TRADEMARKS BASED ON LAW NUMBER 20 OF 2016: A STUDY ON PHILADELPIA BALI AND BLUE PLATE BINTARO - Pati Matu Zahrah; Tahasak Sahay; Andika Wijaya (RADJA PUBLIKA, 2026)
This study examines potential plagiarism involving trademarks and trade concepts in the case of Philadelpia Sushi Bali and Blue Plate Sushi Bintaro based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Using a normative legal approach, the research analyzes similarities in visual elements, promotional strategies, and brand identity that may cause consumer confusion. The findings indicate that similarities in logos, product displays, and digital communication styles can be considered trademark infringement when they replicate the distinctive features of a prior brand. Legal protection for trademarks therefore extends beyond names to include the visual expressions and trade concepts forming the business identity.